PROBLEMS IN TEACHING ENGLISH TO DEAF STUDENTS: A CASE STUDY IN SLB NEGERI SIAK - Annisaq, Annisaq; Supriusman, Supriusman; Syafrianti, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The objectives of the research were to find out the problems faced by the teacher in the process of teaching English to the deaf students and how to overcome the problems. The research object were the first grade deaf students of SLB Negeri Siak and the subject of this research was an English teacher of SLB Negeri Siak. This qualitative research used a case study method. The data were collected by using interview. The researcher used member checking technique to show the trustworthiness of the data. The results of this research showed that the problem that teacher faced varies and the most crucial problem is the abilities of the students heterogeneous. Based on the theory of Thompson (2012) the teacher has followed the instruction to teaching for deaf student by following her own way to solve the problem.Key Words: Problems, Teaching English, Deaf Students